Volume 9: Rodney Eatock Taylor Honoring Symposium on Marine and Offshore Hydrodynamics; Takeshi Kinoshita Honoring Symposium On 2019
DOI: 10.1115/omae2019-95148
|View full text |Cite
|
Sign up to set email alerts
|

Numerical and Experimental Modelling of Wave Loads on Thin Porous Sheets

Abstract: This work considers the numerical modelling of wave interaction with thin porous structures, based on tests conducted in simplified conditions. Wave flume tests were conducted to measure the wave loads on thin porous sheets extending over the full water column. The porous sheets tested had a range of porosities, hole separation distances and thicknesses. Numerical and analytic models for the wave forces on the porous sheet are formulated under the assumptions of either a linear or quadratic pressure loss acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…However, a constant value of δ = 0.5 has been used in the present work. This value was found to give good agreement between experimental results and predictions from a potential-flow model by Mackay et al (2019).…”
Section: Theoretical Pressure-drop Modelsupporting
confidence: 65%
See 1 more Smart Citation
“…However, a constant value of δ = 0.5 has been used in the present work. This value was found to give good agreement between experimental results and predictions from a potential-flow model by Mackay et al (2019).…”
Section: Theoretical Pressure-drop Modelsupporting
confidence: 65%
“…Since differences in the measured wave height between the deeper section and the raised section have been observed, it is hypothesized that it generates a diffracted wave field that interacts with the reflected wave from the porous sheet and cylinders. The effect is discussed further by Mackay et al (2019) who also found discrepancies with a potential-flow model.…”
Section: Physical Experimentsmentioning
confidence: 88%
“…Therefore, the present work assumes the influence of KC to be negligible and uses δ = 0.5. This value was found to have good agreement between experimental results and numerical results from both previous CFD modelling, [33], and from a potential-flow model by Mackay et al [40].…”
Section: Theoretical Pressure-drop Formulationsupporting
confidence: 82%
“…This work focuses on the comparison between CFD models with different types of porosity implementations, but experimental results are included for reference. For detailed information and photos of the experiments, we refer to [33,40,41], but relevant aspects of the setup are outlined in the following.…”
Section: Wave Flume Experimentsmentioning
confidence: 99%
“…The quadratic pressure drops were considered by researchers in prediction of the added mass and the damping coefficients for a porous stabilizer, plate, or disc undergoing forced motions as well as the wave force on thin porous sheets. Examples include Molin and Remy [13] and Mackay et al [14].…”
Section: Introductionmentioning
confidence: 99%